Altered red blood cell deformability—A novel hypothesis for retinal microangiopathy in diabetic retinopathy. (11th August 2020) - Tan, Justin Kok Soon; Wei, Xin; Wong, Peter Agustinus; Fang, Jie; Kim, Sangho; Agrawal, Rupesh
Abstract: Purpose: Impaired red blood cell (RBC) deformability impedes tissue perfusion. This study aims to investigate RBC biomechanics in type 2 diabetes mellitus (DM) patients with different grades of diabetic retinopathy (DR) and to correlate RBC deformability with hematological and serum biochemical markers. Methods: This cross‐sectional study included 86 type 2 DM patients (31 with no DR, 31 with non‐proliferative DR [NPDR] and 24 with proliferative DR [PDR]) and 32 control subjects. RBC deformability was measured by a microfluidic cross‐slot channel (elongation index, EI). Venous blood samples were taken for assessment of hematological and serum biochemical markers. Results: RBC deformability showed significant reduction in diabetic patients, being lowest in the PDR group, followed by NPDR and DM with no DR groups, and highest in control group ( P = .018). RBC deformability was not affected by age or gender but showed significant associations with certain hematological and serum biochemical markers. In the regression analysis controlling for DM status, urea concentration and reticulocyte count were shown to be negatively associated with EI. Conclusion: Impaired RBC deformability measured by a microfluidic cross‐slot channel in DM patients with different grades of DR underscores the contribution of RBC rheological properties to the pathogenesis and progression of DM related microangiopathy.